First Aid Education Media for Fracture Victims Through Android Applications on Student Knowledge - Jupita Suria Ningsih; Leo Fatryanto; Mather (Jurnal teknologi Kesehatan Borneo, 2022)
Heavy traffic increases the number of accidents. One of the accidents resulted in a fracture. High school students are competent to be trained, where they coexist with the broader community, enabling them to become victims or helpers in emergencies. This study aims to determine the effect of first aid education for fracture victims with android application media on the knowledge of the members of the Youth Red Cross at SMAN 3 Sukadana. This research is a quasi-experiment with a pre and post-test control group design model. The number of samples, as many as 26 people,e were divided intotwo2 groups. The results showed that the mean value for the pretest intervention group was 31.,31 with a standard deviation of 11.77. Meanwhile, the posttest means 90.15 with a standard deviation of 9.71. The difference between the mean pretest and posttest was -58.846 with a standard deviation of 10.792, 95% CI -65.367 - -52.324, and p 0.000. The mean value for the pretest control group was 34.31, with a standard deviation of 5.97. While the post-test mean is 40.46 with a standard deviation of 10.82. The mean pretest and posttest were -6,153 with a standard deviation of 12,661, 95% CI -13,804 - 1.497, and p 0.105. This study concludes that there is a significant effect on first aid education for fracture victims using android application media on the knowledge of PMR members of SMAN 3 Sukadana with p = 0.000 (<0.05).